2016
DOI: 10.1021/acs.bioconjchem.5b00481
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase P Mediated Targeting for Breast Tissue Specific Conjugate Delivery

Abstract: Cytotoxic chemotherapies are used to treat breast cancer, but are limited by systemic toxicity. The key to addressing this important issue is the development of a nontoxic, tissue selective, and molecular specific delivery system. In order to potentially increase the therapeutic index of clinical reagents, we designed an Aminopeptidase P (APaseP) targeting tissue-specific construct conjugated to a homing peptide for selective binding to human breast-derived cancer cells. Homing peptides are short amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…(21) In the present study it was found that there were an increase in the weight of women with breast cancer more than that of the control group. The mean of BMI in breast cancer women that show in table (3), this finding was consistence with Platet N. et al (22) and Rebbeck R. et al (23) who reported a high prevalence of overweight and obesity in women with breast cancer. Epidemiological studies have shown that postmenopausal obesity causes an increase in the risk of breast cancer, (24) since the obesity has a close relationship with increased levels of insulin and insulin like growth factors.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…(21) In the present study it was found that there were an increase in the weight of women with breast cancer more than that of the control group. The mean of BMI in breast cancer women that show in table (3), this finding was consistence with Platet N. et al (22) and Rebbeck R. et al (23) who reported a high prevalence of overweight and obesity in women with breast cancer. Epidemiological studies have shown that postmenopausal obesity causes an increase in the risk of breast cancer, (24) since the obesity has a close relationship with increased levels of insulin and insulin like growth factors.…”
Section: Discussionsupporting
confidence: 80%
“…(11) Alanine aminopeptidase spreads in various regions of mammalian body, because it is responsible for many physiological functions inside the human body, like kidney, pancreas, liver, (12) and intestine specially in duodenum. (13) Aggrecan (ACAN) is a proteoglycan that present in all cellular and tissue compartments. It is one of the major structural component of cartilage therefore it is known as cartilage-specific proteoglycan core protein (CSPCP) or chondroitin sulfate proteoglycan 1 (may have >100 chondroitin sulphate chain) which are key to its function in the maintenance of a hydrated, compression-resisting matrix.…”
Section: Introductionmentioning
confidence: 99%